Visualising the endothelial glycocalyx in dogs. (July 2022) - Lawrence-Mills, Sara J.; Neal, Chris R.; Satchell, Simon C.; Welsh, Gavin I.; Foster, Rebecca R.; Finch, Natalie
Abstract: The endothelial glycocalyx (eGlx) lines the luminal surface of endothelial cells. It is critical in maintaining vascular health and when damaged contributes to many diseases. Its fragility makes studying the eGlx technically challenging. The current reference standard for eGlx visualisation, by electron microscopy using glutaraldehyde/Alcian blue perfusion fixation, has not been previously reported in dogs. Established techniques were applied to achieve visualisation of the eGlx in the microvasculature of reproductive tissue in five healthy dogs undergoing elective neutering. Uterine and testicular artery samples underwent perfusion fixation, in the presence of Alcian blue, prior to transmission electron microscopy imaging. Image processing software was used to determine eGlx depth. EGlx was visualised in the arteries of two dogs, one testicular and one uterine, with median (range) eGlx depths of 68.2 nm (32.1–122.9 nm) and 47.6 nm (26.1–129.4 nm) respectively. Study of the eGlx is technically challenging, particularly its direct visualisation in clinical samples. Further research is needed to develop more clinically applicable techniques to measure eGlx health. Highlights: Canine glycocalyx has not previously been visualised using the reference technique. The endothelial glycocalyx was visualised in dog uterine and testicular arteries. Direct visualisation of the endothelial glycocalyx was technically challenging.